Female Genital Mutilation/Cutting (FGM/C) for The Harmony of Sexual Relationship by Islamic Law Perspective - Nurun Sariyah; Abdul Aziz; Aspandi Aspandi; Ahmad Fathan Aniq (Tribakti: Jurnal Pemikiran Keislaman, 2023)
The practice of female circumcision or FGM/C (Female Genitalia Mutilation/Cutting) in Indonesia is stated as a purification process by removing najis or dirt in female genital area and it is useful for controlling women's sexual desires so that they are far from evil. Based on this motivation, FGM/C makes women increasingly subordinated by placing the assumption of infertility and being responsible for the satisfaction of sexual relations with their partners. Apart from tradition, this phenomenon is also based on the strong influence of Islamic religious doctrine which generally makes parents feel compelled to fulfill it. Through a qualitative approach with descriptive-analytical methods, this research will compile and explain the data that has been obtained to be analyzed and drawn conclusions. The results of this study indicate that there is no concrete evidence that correlates female circumcision with sexual harmony, female circumcision is purely a tradition and not an Islamic teaching.